Gene-based therapies for hemophilia - Melissa F. Glasner; Steven Pipe; Wolfgang Miesbach (Research and Practice in Thrombosis and Haemostasis)
Gene therapy is a transformative approach to treating genetic disorders in order to improve disease outcomes for patients. Hemophilia A and B are inherited genetic disorders caused by mutations in the FVIII and FIX genes, respectively. Traditional treatments for hemophilia have included intravenous plasma, factor concentrates, and nonfactor therapies that require lifelong prophylaxis and carry risks of factor inhibitor development. Gene therapy offers a novel solution by delivering functional FVIII or FIX genes via adeno-associated virus vectors, which enable the production of the missing factors. Clinical outcomes have shown promise through gene therapies like valoctocogene roxaparvovec for hemophilia A and etranacogene dezaparvovec and fidanacogene elaparvovec for hemophilia B. Each therapy has demonstrated efficacy in reducing bleeding rates and maintaining factor activity. However, challenges such as hepatotoxicity, immune response, and durability of gene expression persist. Future advancements aim to expand eligibility, achieve sustained expression, and minimize adverse effects. Current trials are exploring new vectors, transgenes, and methods to overcome existing limitations. Gene therapy holds the potential to revolutionize hemophilia treatment, offering a path toward long-term management and improved quality of life for patients.